Effects of glycerol hyperhidration on the running economy of long-distance runners: a randomized crossover clinical trial - Herrera-Amante, Carlos Abraham; García-Zepeda, Gustavo; García-Zepeda, Carlos Eduardo; Yáñez-Sepúlveda, Rodrigo; Clemente-Suárez, Vicente Javier; López-Gil, José Francisco; Octavio Ramos-García, César (Frontiers in Nutrition, 2025)
BackgroundEndurance athletes experience significant water loss during exercise, which can impair performance and increase the risk of dehydration. Glycerol hyperhydration has been explored as a strategy to enhance pre-exercise hydration, particularly when fluid intake opportunities are limited. This study aimed to evaluate the effects of glycerol hyperhydration on running economy (RE) in trained runners.MethodsA randomized crossover clinical trial was conducted with 30 trained runners (15 men, 15 women) across three sessions. In the first session, peak oxygen uptake (VO₂peak) was determined to establish individualized running speeds for the subsequent tests. In the second and third sessions, participants performed submaximal running tests under two conditions: euhydration (control) and glycerol-induced hyperhydration. The glycerol protocol consisted of ingesting 1.2 g/kg body mass of glycerol diluted in 22 mL/kg of water, 120 min before exercise. The assessed variables included caloric cost unit (CCU), oxygen cost unit (OCU), heart rate (HR), body temperature (BT), and rating of perceived exertion (RPE). Effect sizes were calculated using standardized mean differences (Cohen’s d).ResultsGlycerol supplementation significantly improved running economy, reducing CCU (p = 0.025, d = 0.43), OCU (p = 0.011, r = 0.46), HR (p = 0.029, d = 0.42), and RPE (p = 0.003, d = 0.60). Although BT showed a slight decrease (p = 0.053, d = 0.37), it did not reach statistical significance, suggesting a trend toward improved thermoregulation.ConclusionThese findings indicate that glycerol supplementation enhances key metabolic and physiological factors associated with running economy, including CCU, OCU, cardiovascular responses, and perceived exertion in trained runners.Clinical trial registrationhttps://clinicaltrials.gov, identifier: NCT06818253.